Peningkatan Aksesibilitas dan Perbaikan Fasilitas Umum di Lingkungan RT 02 RW 14 Manukan Subur, Kelurahan Manukan Kulon, Kecamatan Tandes, Kota Surabaya - Failasuf Herman Hendra; Annisa Nur Ramadhani (Institut Teknologi Adhi Tama Surabaya, 2022)
Place accessibility of a settlement has a significant contribution to mobility, communication to the productivity of residents. Place accessibility can be increased with the capacity and improvement of existing public facilities as one of the aspects that affect it. In the area of RW 14 Manukan Subur, Manukan Kulon Village, Tandes District, Surabaya City, there are several Gang Kampungs that have low accessibility due to environmental infrastructure such as village roads that are starting to deteriorate, city drains are clogged and entrance gates to villages are not easily recognizable. Also public facilities that are poorly maintained as a result of the Covid-19 pandemic, where residents limit activities outside the home so that interaction between residents is greatly reduced. Public facilities that are starting to look dull and not maintained have also caused residents to be reluctant to use them. Community service activities by making improvements to public facilities with residents are expected to be a trigger in increasing interaction between residents as before. The implementation of the activities consists of a preparation stage in the form of site surveys and interviews, implementation stages, and evaluations. The focus of the activities is on repairing city drains and its cover, designing the gate, improving the environment and redesigning the RT Hall for future functions. The existence of community service activities is expected to contribute to increasing the place accessibility for an area.